Meaning, personal purpose and the Big Five personality traits in exploring leader effectiveness in South Africa’s FMCG sector during the Fourth Industrial Revolution - Moloko Lebohang Duduzile; Toendepi Joyce (Journal of Economics and Management, 2025)
Aim/purpose – Effective leadership in the Fourth Industrial Revolution (4IR) era requires the right mix of personality traits, a deep sense of meaning, and personal purpose. The Big Five personality traits theory was chosen for its cross-cultural applicability and effectiveness in describing various personality traits precisely. The study had a two-fold objective: first, to explore the impact of meaning and personal purpose on the effectiveness of leaders in the fast-moving consumer goods (FMCG) sector in South Africa (SA) during 4IR era, and second, to understand how meaning and personal purpose are embedded within the Big Five personality traits.